Are Humans Safe in Public Places? Expansion of Protection Motivation Theory in the Gulf Cooperation Council Countries (Central Asian Journal of Medical Sciences, 2019)
Objectives: People regularly face safety threats that are often ignored in day to day life. The knowledge and understanding of the risks posed through unhealthy activities are essential. This realization can change behavior in ways that are effective in mitigating risk. The study aimed to determine the importance of protection motivation theory in studies conducted in Saudi Arabia, Kuwait, the United Arab Emirates, Qatar, Bahrain, and Oman evaluating the safety and health concerns of people living in the region. Methods: This study reviews previous studies that analyzed social protection motivation theory constructs to analyze and improve the health and safety in these countries. Results: Several studies were identi ed, indicating that the protection motivation theory is important in motivating individuals to change behavior. Conclusion: Protection motivation theory is a useful construct to understand and mitigate risk. It can aid in developing preventive measures to enhance individual safety.